The Genetic and Epigenetic Journey of Embryonic Stem Cells into Mature Neural Cells - Olynik, Brendan; Rastegar, Mojgan (Frontiers in Genetics, 2012)
From embryo to adult, epigenetic changes occur throughout the life of an organism, resulting in the timely expression or repression of developmental genes and their transcript products. Whereas the field of genetics primarily concerns itself with nucleic acid sequence, epigenetics refer to inheritable changes in gene expression and cellular phenotype without altering the underlying DNA sequence. Multiple epigenetic modifications are important in neural development including the addition of various groups to histone proteins, direct methylation and hydroxymethylation of cytidine nucleotides in DNA, and activities of non-coding RNAs. The goal to use stem cells for regenerative medicine, such as in neurodegenerative diseases, requires an appreciation of the involved epigenetics. In this review, we will introduce the role of stem cells in development, followed by a background to epigenetic modifications, describing the key genetic and epigenetic events that ensue as embryonic stem cells (ESC) properly follow the path towards specific neural cell types.